Hemotherapy: phenotype red blood cells for sickle cell patients - Andrade, Simone Possas (2018)
Hemotherapy is a means of treating sickle cell anemia, with the most commonly used phenotype red blood cell transfusions. Sickle cell anemia, to this day, is a challenge for its patients and professionals in the field, because there is a great difficulty in pathophysiological processes and because of the severity of many of its clinical manifestations. It is therefore important that the disease is detected early. The biomedical professional is one of the main responsible for this, as it is qualified to perform the clinical exams in order to diagnose and clarify the actual clinical picture and the appropriate treatment for disease. The aim of the study is to report the importance of hemotherapy in sickle cell patients, with emphasis on the importance of phenotyped red blood cell concentrates for sickle cell patients. Erythrocyte immunophenotyping in patients with sickle cell anemia is important in order to prevent one of the main complications of transfusion therapy, since the presence of alloantibodies and autoantibodies leads to the obtaining of compatible blood and can cause acute or late hemolytic transfusion reactions, increasing the morbidity of the disease. Thus, for the treatment and correct diagnosis, there are numerous exams, the most used and qualified being the foot test (used for a pre-diagnosis); the hemogram; and hemoglobin electrophoresis in cellulose acetate or in agarose, with a pH ranging from 8 to 9, which is the most qualified technique to confirm the diagnosis of this hemoglobinopathy.